2018
DOI: 10.1097/ajp.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Low Back Pain in Childhood and Adolescence

Abstract: Future studies should focus on muscle characteristics, the relationship between body and backpack weights, duration of carrying the backpack, characteristics of sport practice, and which are the factors associated with specifically chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 75 publications
5
64
1
14
Order By: Relevance
“…Third, a misclassification on the self‐report of comorbidity and painful TMD may be considered. However, Figure shows that the percentage of comorbidities found in this study are in the range of those noted in the systematic reviews . In addition, Graue et al noted that the estimated prevalence of painful TMD was lower when using self‐reported screening questionnaires than when using DC/TMD criteria, suggesting that use of self‐reported questionnaires may provide a conservative estimate of painful TMD prevalence.…”
Section: Discussioncontrasting
confidence: 38%
“…Third, a misclassification on the self‐report of comorbidity and painful TMD may be considered. However, Figure shows that the percentage of comorbidities found in this study are in the range of those noted in the systematic reviews . In addition, Graue et al noted that the estimated prevalence of painful TMD was lower when using self‐reported screening questionnaires than when using DC/TMD criteria, suggesting that use of self‐reported questionnaires may provide a conservative estimate of painful TMD prevalence.…”
Section: Discussioncontrasting
confidence: 38%
“…Many factors have been suggested to be associated with a higher risk of LBP among schoolchildren (Calvo‐Muñoz, Kovacs, Roqué, Gago Fernández, & Seco Calvo, ), including biological (e.g., body weight, weight bearing, muscle strength or ergonomics) (Fairbank, Pynsent, Poortvliet, & Phillips, ; Sano et al, ; Yamato, Maher, Traeger, Wiliams, & Kamper, ), psychosocial (e.g., family and social relations or satisfaction with school) (Dianat, Alipour, & Asghari Jafarabadi, ; Mikkonen et al, ) and lifestyle related variables (e.g., physical activity, participation in sports or smoking) (Kovacs et al, ; Wedderkopp, Leboeuf‐Yde, Bo Andersen, Froberg, & Hansen, ).…”
Section: Introductionmentioning
confidence: 99%
“…A prevalência de dor lombar crônica entre os adolescentes com DL pode ser considerada alta, o que é preocupante nesta etapa da vida, uma vez que sintomas crônicos são associados à incapacidade entre adultos 3 . A associação entre sexo feminino e DL nos últimos 12 meses é consistente com a literatura, mesmo entre estudos que utilizam diferentes períodos de recordatório para caracterização do desfecho 4,20 . Estes resultados podem refletir diferenças estruturais e psicossociais entre os sexos, sendo que as mulheres podem relatar a dor com maior frequência do que os homens.…”
Section: Métodosunclassified
“…A maior sobrecarga sobre a coluna vertebral devido aos longos períodos sentados e o carregamento de peso que aumentam na medida em que os adolescentes se tornam mais velhos pode explicar a associação linear direta entre idade e o desfecho 4,7,8,21 . Não foram encontrados estudos que avaliem a associação entre maior renda e DL no último ano, sendo que apenas um estudo brasileiro avaliou a relação entre nível socioeconômico e DL, mas não encontrou diferença significativa 7 .…”
Section: Métodosunclassified
See 1 more Smart Citation